Descriptive Memoir of the Ministry of Information and Broadcasting, January 1956 - Planning Commission (Planning Commission, 1956)
The Ministry of Information and Breasting was created in October, 1941. It is charged with the responsibility for public and broadcasting activities of the Government of India and the general conduct of Government relations with the press. The following functions of the Ministry of Information and Broadcasting fall within the Union List:- (i) Broadcasting; (ii) Sanctioning of cinematograph films for exhibition. Description of Service Actually Rendered by the Ministry The various activities of the Ministry and the important services rendered by it are briefly described under the following heads
Organisation and Methods Division Cabinet Secretariat